2005
DOI: 10.1111/j.1572-0241.2005.40377.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Associated Coronavirus Is Detected in Intestinal Tissues of Fatal Cases

Abstract: In addition to the lungs, the gastrointestinal tract is another target of SARS-CoV infection, as the intestinal epithelial cells and mucosal lymphoid tissue are infected. The findings provide possible explanations for the gastrointestinal symptoms and the presence of virus in the stool of SARS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 27 publications
2
96
0
Order By: Relevance
“…In general, no changes have been evident on gross examination of the digestive system. In some confirmed SARS cases, mild diffused inflammation of the digestive tract, together with autolytic changes have been reported Shi et al, 2005;, whereas other authors have reported no histological abnormalities (Lang et al, 2003;Leung et al, 2003). The most prominent histopathological change, which has been reported in the digestive tract, is atrophy of the submucosal lymphoid tissues , which is described in detail in Section 2.2 of this review.…”
Section: Digestive Tractmentioning
confidence: 82%
See 1 more Smart Citation
“…In general, no changes have been evident on gross examination of the digestive system. In some confirmed SARS cases, mild diffused inflammation of the digestive tract, together with autolytic changes have been reported Shi et al, 2005;, whereas other authors have reported no histological abnormalities (Lang et al, 2003;Leung et al, 2003). The most prominent histopathological change, which has been reported in the digestive tract, is atrophy of the submucosal lymphoid tissues , which is described in detail in Section 2.2 of this review.…”
Section: Digestive Tractmentioning
confidence: 82%
“…Liver tissues of SARS autopsies have shown numerous hepatocyte mitoses, balloon degeneration of hepatocytes and mild to moderate lymphocytic infiltrates (Chau et al, 2004;Lang et al, 2003). Fatty degeneration and central lobular necrosis have also been reported (Ding et al, 2003;Gu et al, 2005;Lang et al, 2003;Shi et al, 2005). Apoptosis was evident in all three SARS cases reported by Chau et al (2004).…”
Section: Livermentioning
confidence: 83%
“…The virus may be present in anal swabs or blood of patients when oral swabs detection negative. In SARS-CoV and MERS-CoV infected patients, intestinal infection was observed at later stages of infection [7][8][9]. However, patients infected with 2019-nCoV may harbour the virus in the intestine at the early or late stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of SARS-CoV in intestinal tissue of fatal SARS cases indicated that the gastrointestinal tract is another tar-get for SARS-CoV infection [38]. Hence, a vaccine candidate should ideally induce protective response in mucosal sites.…”
Section: Mucosal Igg and Iga Response In Micementioning
confidence: 99%